2009
DOI: 10.1002/mds.22767
|View full text |Cite
|
Sign up to set email alerts
|

Loss of nocturnal blood pressure fall in various extrapyramidal syndromes

Abstract: Cardiovascular autonomic dysfunction has frequently been reported in some patients with extrapyramidal syndromes, especially multiple system atrophy (MSA) but also Parkinson's disease (PD). However, there are only few reports on the prevalence of cardiovascular autonomic dysfunction progressive in supranuclear palsy (PSP). Moreover, the relation of detailed cardiovascular testing and easy to assess 24-hour ambulatory blood pressure (BP) is not known. Our study evaluates 24-hour ambulatory BP monitoring in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 26 publications
3
75
0
5
Order By: Relevance
“…8 These abnormalities are related to each other. SH is found in a substantial proportion of patients with PD with OH.…”
mentioning
confidence: 97%
“…8 These abnormalities are related to each other. SH is found in a substantial proportion of patients with PD with OH.…”
mentioning
confidence: 97%
“…6-8 Many patients with autonomic failure have both OH and a nondipping BP pattern. 10 Circadian patterns of BP have not been well studied among individuals with OH. Moreover, there is little data relating postural BP changes to nocturnal BP changes.…”
mentioning
confidence: 99%
“…They also found that all of the PD patients had postprandial hypotension and nocturnal hypertension. Schmidt et al observed a similar pathological nocturnal blood pressure regulation [55]. Usually, the mean arterial pressure decreases by 10%-20% during sleep, compared to the waking time.…”
Section: Autonomic System Dysfunctionsmentioning
confidence: 81%